Energy-Efficient Coverage Guarantees Scheduling and Routing Strategy for Wireless Sensor Networks. (26th August 2015) - Le, Nam-Tuan; Jang, Yeong Min
Abstract : With the development of semiconductors and the resulting effect on manufacturing costs, wireless interface platforms have become increasingly powerful and popular. This has resulted in widespread applications ranging from daily life activities to military services. In large-scale applications of wireless sensor networks such as military surveillance, there are two important issues that determine the success of network services. The first is sensing coverage, the data collection process from the target that directly affects network traffic. The second is network lifetime which is based on the optimization of energy consumption. Power optimization for mobile platforms can be classified into two categories: efficient power based on protocol and extended interface. In this paper, we suggest an energy model for wireless sensor networks that is based on the first issue; it can be called Coverage and Energy Strategy for wireless sensor networks (CESS). The scheme will attempt to achieve optimal coverage of the sensing area and energy balanced scheduling for all sensors. It can reduce redundancy of working sensor nodes by defining minimal number of active nodes in a sensing area. Thus the network lifetime will be maximized by reducing redundancy power consumption.